2019
DOI: 10.1152/jn.00003.2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cortex in visuomotor control of arm stability

Abstract: Whereas numerous motor control theories describe the control of arm trajectory during reach, the control of stabilization in a constant arm position (i.e., visuomotor control of arm posture) is less clear. Three potential mechanisms have been proposed for visuomotor control of arm posture: 1) increased impedance of the arm through co-contraction of antagonistic muscles, 2) corrective muscle activity via spinal/supraspinal reflex circuits, and/or 3) intermittent voluntary corrections to errors in position. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
(160 reference statements)
3
2
0
Order By: Relevance
“…We found an increasing tendency of alterations of nodal properties in the non-deficit group and an unchanging tendency in the deficit group compared with the healthy group. This finding further verified that the contralesional sensorimotor cortices are crucial for motor functional compensation (47,48). Moreover, our results showed that, regardless of the glioma location, the nodal efficiency, nodal clustering coefficient, and nodal local efficiency of the nodes (premotor-related thalamus) increased in the non-deficit group and decreased in the deficit group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found an increasing tendency of alterations of nodal properties in the non-deficit group and an unchanging tendency in the deficit group compared with the healthy group. This finding further verified that the contralesional sensorimotor cortices are crucial for motor functional compensation (47,48). Moreover, our results showed that, regardless of the glioma location, the nodal efficiency, nodal clustering coefficient, and nodal local efficiency of the nodes (premotor-related thalamus) increased in the non-deficit group and decreased in the deficit group.…”
Section: Discussionsupporting
confidence: 86%
“…These findings indicated that the premotor-related thalamus played an important role in compensating for the damaged motor function in the nondeficit stage and significantly decreased the conveying efficiency in the deficit stage. Previous studies showed that the contralesional motor-related thalamus participated in motor plasticity by changing pathways and building midline-crossing contralesional corticospinal fibers (47,48). Hence, our findings verified this theory through functional networks and differed from previous verification through structural networks.…”
Section: Discussionsupporting
confidence: 53%
“…;Formaggio et al 2013;Snyder et al 2019), but there is also evidence of ipsilateral hemispheric involvement during a motor task, as shown in our study. Chen et al used repetitive Transcranial Magnetic Stimulation (rTMS) to brie y disrupt the ipsilateral motor cortex during a sequence of nger movements and found timing errors even with simple sequences (Chen et al 1997), suggesting that both hemispheres contribute to a simple motor task.…”
supporting
confidence: 88%
“…We collected EEG data while participants moved their index nger. During and at the end of the task, we quanti ed cortical activation using the change in EEG power relative to baseline in the beta band (13-26Hz) (Stancák and Pfurtscheller 1996; Pfurtscheller and Lopes da Silva 1999) and quanti ed connectivity between cortical areas using task-based coherence between EEG electrodes (Rappelsberger et al 1994;Gerloff et al 2006;Snyder et al 2019). We hypothesized that: 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between the ability to maintain hand position and the performance of ADLs in patients with schizophrenia is not fully understood. A previous neurological study reported functional connectivity between the sensorimotor cortex and the visual cortex during arm posture maintenance, suggesting that motor commands are adjusted based on sensory information [15]. Patients with schizophrenia show sensorimotor coordination dysfunction [16].…”
Section: Positional Stability Of the Non-dominant Hand Is Associated ...mentioning
confidence: 99%